The Influence Of Information Technology And The Perception Of Usefulness On The Use Of E-Filing - Setya Nusa, Inta Budi; Dubovick, SnjeÅ¾ana (International Journal of Artificial Intelligence Research, 2021)
This present study at identifying the influence of information technology toward the use of e-Filing and the influence of perception of usefulness toward the use of e-Filing. The research method used is descriptive and verification with quantitative approach. The data used is primary data, while data collection techniques used are field research and library research. The sample in this research are 34 individual taxpayers of Weat Java Provincial Secretariat Office. The analysis model used is SEM PLS. The results of this study show that information technology has an effect on the use of e-Filingand usability perception has an effect on the use of e-Filing